Norman Didn't Do It! : (yes, he did.) - Higgins, Ryan T. (Los Angeles ; New York : Disney\Hyperion, 2021)
Norman, a porcupine whose best friend is a tree named Mildred, begins to feel jealous when another tree grows close to Mildred and acts out against the new tree.
Ages 3-5.
Grades K-1.
Keywords: Trees -- Fiction; Porcupines -- Fiction; Friendship -- Fiction; Jealousy -- Fiction